Weight Stigma Experiences and Physical (In)activity: A Biographical Analysis - Ansgar Thiel; Jannika M. John; Johannes Carl; Hendrik K. Thedinga (Obesity Facts, 2020)
Introduction: People with obesity often report experiences of weight-related discrimination. In order to find out how such experiences throughout the life course are related to physical activity behavior, we exploratively studied activity-related biographies of people with obesity from a social constructivist perspective. Methods: We collected biographical data of 30 adults (mean age 37.66 years; 14 males and 16 females) with obesity (average BMI 40.64, including a range from 33 to 58) using a biography visualization tool that allows participants to map developmental courses and critical life experiences over their life course. Results: Participants remembered a continuous decrease of physical activity from childhood to mid-adulthood. Weight-related discrimination, both in sport and non-sport settings, was especially experienced in adolescence and mid-adulthood. Against the background of our findings, we assume that the degree of felt stigma rather than the stigmatizing behavior itself influences physical activity behavior over the life course. Conclusion: The results of our exploratory study reiterate the detrimental effect weight stigma can have on health behaviors. Initiatives are needed to reduce weight stigma in exercise contexts; additionally, initiatives to promote physical activity should focus on helping individuals with obesity to establish coping strategies to reduce the experienced burden from weight stigma.